The prodigal sun - High, Philip E.; Ace Books (Ace, 1964)
Foster child of the Mattrain - planet of supermen - Duncan returned to Earth, his birthplace, only to meet suspicion, hostility and hatred. Upon arrival, he was engulfed by an angry populace who, fearing that he was a spy, welcomed him with jeers and signs saying, ALIEN GO HOME! To Duncan this reception was not unexpected. He had come, not for his pleasure, but for a purpose - his was a mission on whose success hinged the existence of the whole human race.
"First book publication."
"F-255 Ace Book"--Cover.
Novel.
Reginald, R. Science fiction,07189
Foster child of the Mattrain - planet of supermen - Duncan returned to Earth, his birthplace, only to meet suspicion, hostility and hatred. Upon arrival, he was engulfed by an angry populace who, fearing that he was a spy, welcomed him with jeers and signs saying, ALIEN GO HOME! To Duncan this reception was not unexpected. He had come, not for his pleasure, but for a purpose - his was a mission on whose success hinged the existence of the whole human race.
Keywords: Science fiction, English. / fast / (OCoLC)fst01108670; Science fiction, English.; Science fiction. / fast / (OCoLC)fst01726489; Science fiction. / lcgft